Pengaruh Likuiditas, Leverage, dan Manajemen Laba Terhadap Agresivitas Pajak (Studi Empiris pada Perusahaan Infrastruktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022) - yuniar rahmawaati; Aloysius Harry Mukti; Triana Yuniati (Draf Solusi Indonesia, 2024)
This research aims to test and analyze the impact of liquidity, leverage, and profit management on tax aggressiveness on infrastructure companies listed on the Indonesia Stock Exchange in 2019-2022. This study used a quantitative method with secondary data sources using data in the form of annual corporate reports. The sampling technique used is purposive sampling method and obtaining as many as 95 samples. The analysis methods used are descriptive statistical analysis, classical assumption test, correlation test, multiple linear regression test and hypothesis test. The results of this study show that liquidity and leverage have no effect on tax aggressiveness. Profit management has a positive effect on tax aggressiveness